Exposer l’intérieur domestique : le cas de la salle Boucher de la Frick Collection - Marchand, Marie-Ève (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2020)
This article looks at the (re-)presentation of the domestic interior in museums by means of the period room. It focuses on the spatial complexity of this exhibition strategy to deepen our understanding of the process by which interiors from the past are museumified. Through an examination of the Boucher Room on display at the Frick Collection, New York, this study first challenges the principle of spatial unity which traditionally governs the period room before exploring how the relationship between the period room and its exhibition site informs the version of the history of the domestic interior offered to visitors. By bringing to light the distinctive features of this exemplary case, at once displaced and in situ, this study shows the potential contribution of the notion of space to the development of new perspectives on the interiors of the past and the modalities of their presentation within museums.